Administrative Justice of France and Ukraine: a comparative legal analysis - Гетьман, Євген Анатолійович; Гетьман, Катерина Олегівна (Theory and practice of jurisprudence, 2019)
The article is devoted to a comparative legal analysis of the administrative proceedings in France and Ukraine. The structure of administrative justice of France, its similar and distinctive features from Ukraine is considered. It was proposed to take over to Ukraine the positive experience of France in the field of consulting by the highest judicial authority – the government, individual ministries and other central executive bodies in the area of management decision-making, including sub-legal regulatory acts. The comparative legal analysis made it possible to conclude that the model of administrative justice of Ukraine has both common and distinctive features with the administrative justice of France. At the same time, one can not speak about their absolute identity. In our opinion, the practice of advising a higher judicial authority - the government, individual ministries and other central executive authorities in the sphere of the adoption of management decisions, including bylaws of normative ones – is a positive and possible one that can be borrowed from administrative court proceedings of Ukraine from the model of administrative legal proceedings of France. -legal acts. This will reduce the number of lawsuits against administrative courts over appeals against decisions, actions or omissions of executive authorities